PENGARUH LATIHAN MODEL PEMBELAJARAN PUKULAN BOLA KE TEMBOK TERHADAP KEMAMPUAN SERVIS ATAS BOLAVOLI PADA SISWA SMK NEGERI 2 MAKASSAR - Sahabuddin, Sahabuddin (UNIVERSITAS NEGERI MAKASSAR, 2018)
This study aims to determine the effect of ball to wall learning model training on top service ability in volleyball games. By using the field experiment method. The population used was students of SMK Negeri 2 Makassar with a sample of 20 male students taken by random sampling. The data analysis technique used was the t-test at a significant level of 95%. The results of the study show that; (1) There is a significant influence on ball-to-wall learning model training on top service ability in volleyball games, proven to be t0 = 7.720> tt = 2.262, and (2) There is a significant difference in influence between ball model training on the wall and group control of top service ability in volleyball games, proved t0 = 4,658> tt = 2,101.